Hybrid flow shop rescheduling algorithm for perishable products subject to a due date with random invalidity to the operational unit - Chen, Wenchong; Li, Jing; Ma, Wentao (International journal of advanced manufacturing technology, 2017)
In China, delivery delays due to a high probability of operational unit failure often occur in perishable manufacturing systems. This paper proposes a rescheduling algorithm known as complete rerouting (CR) for perishable manufacturing systems. The perishable characteristics of agri-products and the stochastic invalidity of operational units are researched. Products and operational units of the system are simulated by agents. In the developed virtual perishable manufacturing system, multiple product agents with different deadlines, values, and due dates search for the best processing route according to scheduling principles. When an operational unit fails stochastically, agents update their status and reroute their path using the rescheduling algorithm. The transition of agents can be described by the Petri net model proposed in this paper. Three basic experiments are investigated, validating the rescheduling algorithm proposed. This study demonstrates that the CR policy causes product agents to search for the best rerouting path compared to other rescheduling policies (i.e., right-shift scheduling and new-job rerouting). The optimal delivery times of products are determined based on penalty cost. Furthermore, this study analyzes the sensitivity of scheduling performance due to different product batches with two failed operational unit statuses (i.e., high frequency, short maintenance, and low frequency, long maintenance).